Superiority of Out-of-Office Blood Pressure for Predicting Hypertensive Heart Disease in Non-Hispanic Black Adults. Issue 5 (November 2019) - Rader, Florian; Franklin, Stanley S.; Mirocha, James; Vongpatanasin, Wanpen; Haley, Robert W.; Victor, Ronald G.
Abstract : Black Americans suffer disproportionately from hypertension and hypertensive heart disease. Out-of-office blood pressure (BP) is more predictive for cardiovascular complications than clinic BP; however, the relative abilities of clinic and out-of-office BP to predict left ventricular hypertrophy in black and white adults have not been established. Thus, we aimed to compare associations of out-of-office and clinic BP measurement with left ventricular hypertrophy by cardiac magnetic resonance imaging among non-Hispanic black and white adults. In this cross-sectional study, 1262 black and 927 white participants of the Dallas Heart Study ages 30 to 64 years underwent assessment of standardized clinic and out-of-office (research staff-obtained) BP and left ventricular mass index. In multivariable-adjusted analyses of treated and untreated participants, out-of-office BP was a stronger determinant of left ventricular hypertrophy than clinic BP (odds ratio per 10 mm Hg, 1.48; 95% CI, 1.34–1.64 for out-of-office systolic BP and 1.15 [1.04–1.28] for clinic systolic BP; 1.71 [1.43–2.05] for out-of-office diastolic BP, and 1.03 [0.86–1.24] for clinic diastolic BP). Non-Hispanic black race/ethnicity, treatment status, and lower left ventricular ejection fraction were also independent determinants of hypertrophy. Among treated Blacks, the differential association between out-of-office and clinic BP with hypertrophy was more pronounced than in treated white or untreated participants. In conclusion, protocol-driven supervised out-of-office BP monitoring provides important information that cannot be gleaned from clinic BP assessment alone. Our results underscore the importance of hypertension management programs outside the medical office to prevent hypertensive heart disease, especially in high-risk black adults. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00344903. Abstract : Supplemental Digital Content is available in the text.